Community Engagement Approach to Successful Malaria Elimination in Kulon Progo District - Heru Subaris Kasjono; Yamtana; Sugianto; Ratna Etika Sintawati (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
This study, conducted in October–November 2024 in Kulon Progo Regency, Indonesia, explores a model of community engagement in supporting malaria elimination in high-case areas. Although malaria remains prevalent in eastern Indonesia, cases continue to occur in Java, including Kulon Progo. Using mixed-methods sequential exploratory design, this study combined qualitative and quantitative approaches. Data was collected through observations, interviews, focus group discussions (FGDs), and questionnaires, involving 200 participants—comprising 100 village officials and 100 community health cadres and members. Quantitative data were analyzed using univariate analysis and path analysis. Findings revealed that knowledge and attitudes significantly affect community participation in malaria elimination activities, such as mosquito breeding site eradication and clean-up programs. The path coefficient score (13.93) indicates that community engagement has a strong influence on environmental improvement. Moreover, cross-sector collaboration enhances program effectiveness. This engagement model demonstrates significant potential in strengthening sustainable malaria elimination efforts in endemic-prone areas.